Do Teachers' Beliefs About Math Aptitude and Brilliance Explain Gender Differences in Children's Math Ability Self-Concept? - Heyder, Anke; Steinmayr, Ricarda; Kessels, Ursula (Frontiers in Education, 2019)
The self-concept of ability in math in elementary school is an early predictor for future math-related choices and careers. Unfortunately, already at this early age girls report lower ability self-concepts in math than boys - despite their comparable performances in objective math competence tests. In the present study we focus on teachers’ beliefs as factors explaining these gender differences. Women’s underrepresentation in math and science in academia has recently been explained by the belief held by the environment that success in these domains requires an innate ability that cannot be taught (“brilliance”). In addition, teachers’ beliefs regarding their students’ mathematical aptitude have also been found to influence students’ self-concepts of ability. Here, we study if teachers’ beliefs regarding their students’ mathematical aptitude and brilliance beliefs may account for gender differences in elementary school students’ self-concept of ability in math and thus potentially contribute to entering the gendered path into math and science professions. In a sample of 830 fourth graders (M = 9.14 years old, 49% female) and 56 elementary school teachers from Germany, we assessed teachers’ beliefs regarding their students’ mathematical aptitude and their belief that children need brilliance to succeed in math as well as children’s mathematical ability self-concept and competencies. In line with prior research, boys reported a statistically significantly more positive math ability self-concept (d = 0.50), although boys and girls reached similar scores in a standardized math competence test (d = 0.07). However, multilevel regression analyses revealed that teachers’ math brilliance beliefs were not related to the gender gap in students’ ability self-concept in expense of girls whereas the gender gap was mediated by teachers’ beliefs about their students’ mathematical aptitude. These findings suggest that math brilliance beliefs held by important socializers such as teachers might not play a role in explaining gender differences in math-related motivation in elementary school whereas teachers’ beliefs about students’ math aptitude do. Results are discussed against the background of teacher expectancy effects, developmental changes in elementary school, and cultural differences.